2020
DOI: 10.3390/agronomy10091242
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Fruit Quality Traits of Different Strawberry Varieties under Variable Environmental Conditions

Abstract: Strawberry fruit quality traits can be affected by genotype–environment interactions, determining the final consumer acceptance of fruits. Trait stability under varying environments is necessary to ensure the fruit quality of strawberries selected by breeding programs. Hence, inter- and intra-annual variation of organoleptic and functional fruit quality parameters of five strawberry varieties throughout four consecutive cropping seasons was analyzed to assess their relative stability. In most varieties, organo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 63 publications
5
38
4
Order By: Relevance
“…Thus, the total anthocyanin contents in strawberry are both qualitatively and quantitatively known to be strongly influenced by the genotype (among others [9][10][11][12][13][14]) and likewise, by external factors such as high or low temperature and light (photoperiod, quantity and wavelength including UV-light). Recent review articles have highlighted the influence of temperature and light on the synthesis and accumulation of plant secondary metabolites including anthocyanins [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the total anthocyanin contents in strawberry are both qualitatively and quantitatively known to be strongly influenced by the genotype (among others [9][10][11][12][13][14]) and likewise, by external factors such as high or low temperature and light (photoperiod, quantity and wavelength including UV-light). Recent review articles have highlighted the influence of temperature and light on the synthesis and accumulation of plant secondary metabolites including anthocyanins [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, strawberry yield and the yield components stayed positively correlated based on either genotypic or phenotypic correlations, but with signi cantly different values. (Cervantes et al, 2020) and (Gabriel et al, 2018) in their study on different strawberry cultivars showed that environment has a great effect on the variability of the traits. Saed-Moucheshi (2018) by focusing on traits' relationship under different environmental conditions showed that under normal condition the variability among traits was higher than that under stress condition, which supports our results of changes in genotypic and phenotypic correlation coe cients.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the availability of genetic diversity within compatible genetic resources, including wild species and domestic cultivars will enhance the extent of any improvement (Lot et al, 2014;Saed-Moucheshi et al, 2021). Breeding value, the amount heritability in a feature, can be deduced from the phenotypic and genotypic value for key desirable traits, as well as from the heritability and genetic advances value of the parental lines (Moucheshi et al, 2011;Vosough et al, 2015;Cervantes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…is a popular species of berry plants, cultivated all over the world. The fruits of this species are highly appreciated as a source of macro-and microelements, vitamins, and prohealth antioxidants [21][22][23]. The annual production in recent years has reached 9.2 Mt [24].…”
Section: Introductionmentioning
confidence: 99%